14.8 MeV Neutron Activation Cross Section Measurements for Ge Isotopes - Haque, M. M.; Islam, M. T.; Hafiz, M. A.; Miah, R. U.; Uddin, M. S. (Journal of Scientific Research, 2009)
The cross sections of Ge isotopes were measured with the activation method at 14.8 MeV neutron energy. The quasi-monoenergetic neutron beams were produced via the 3H(d,n)4He reaction at the 150 kV J-25 neutron generator of INST, AERE. The characteristics γ-lines of the product nuclei were measured with a closed end coaxial 17.5 cm2 high purity germanium (HPGe) detector gamma ray spectroscopy. The cross sections were determined with reference to the known 27Al(n,α)24Na reaction. Cross section data are presented for 72Ge(n,p)72Ga, 74Ge(n,α)71mZn and 76Ge(n,2n)75m+gGe reactions. The cross section values obtained for the above reactions were 24.78±1.75 mb, 1.69±0.11 mb and 860±50 mb, respectively. The results obtained were compared with the values reported in literature as well as theoretical calculation performed by the statistical code SINCROS-II. The experimental data were found fairly in good agreement with the calculated and literature data. Keywords: Activation cross section; Neutron induced reaction; Gamma-ray spectroscopy; 14.8 MeV. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i2.1532